A comprehensive review on small-scale thermal energy harvesters: Advancements and applications. (2022) - Ramkumar, Alajingi; Ramakrishnan, Marimuthu
Abstract: During energy conversion, energy is dissipated and wasted in the form of heat. This energy if recovered reduces the cost per unit of power generation and also ensures higher efficiency of the system. There are multiple systems that can directly convert heat energy into electricity namely, Thermoelectric generator(TEG), Pyroelectric energy harvester(PYEH), Thermomagnetic energy harvester(TMH), Thermoelastic energy harvester (TEH), and Thermionic energy conversion (TIC) systems. The entire transformation of these systems throughout the ages are presented in this work. And also reviews the performance and recent progress of these systems along with their applications in heat recovery. Also, heat energy recovery sources and their matching heat energy conversion systems are discussed. Each model application in converting different energy recovery sources into electrical energy is enumerated along with its research gaps. All system's current and potential future applications in commercial, industrial and other related fields are briefly explained.